2020
DOI: 10.1186/s12964-020-00582-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKCε in the epithelial-mesenchymal transition induced by FGFR2 isoform switch

Abstract: Background: The epithelial isoform of the fibroblast growth factor receptor 2 (FGFR2b) controls the entire program of keratinocyte differentiation via the sequential involvement of protein kinase C (PKC) δ and PKCα. In contrast, the FGFR2 isoform switch and the aberrant expression of the mesenchymal FGFR2c isoform leads to impairment of differentiation, epithelial-mesenchymal transition (EMT) and tumorigenic features. Aim of our present study was to contribute in clarifying the complex network of signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
2
19
2
Order By: Relevance
“…Despite these supporting studies, our current results seem apparently in contrast with the recent findings reported by Basu, which indicate a key role of PKCε in promoting autophagic process in metastatic breast cancer cells 17 . This discrepancy would be explained considering the hypothesis that FGFR2c plays its oncogenic role in the early steps of tumour development, 4‐6 further confirming the dual and opposite contribution of autophagy in different (early and advanced‐metastatic) steps of carcinogenesis 8 . In fact, it has been proposed that autophagy can play a ‘double‐edged sword’ role on EMT, repressing the process in early, but inducing it in late, stages of tumorigenesis 8 …”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite these supporting studies, our current results seem apparently in contrast with the recent findings reported by Basu, which indicate a key role of PKCε in promoting autophagic process in metastatic breast cancer cells 17 . This discrepancy would be explained considering the hypothesis that FGFR2c plays its oncogenic role in the early steps of tumour development, 4‐6 further confirming the dual and opposite contribution of autophagy in different (early and advanced‐metastatic) steps of carcinogenesis 8 . In fact, it has been proposed that autophagy can play a ‘double‐edged sword’ role on EMT, repressing the process in early, but inducing it in late, stages of tumorigenesis 8 …”
Section: Resultscontrasting
confidence: 99%
“…The fibroblast growth factor receptors (FGFR1‐4) are receptor tyrosine kinases regulating key processes, such as cell proliferation, differentiation, migration and survival 1 . The epithelial isoform of fibroblast growth factor receptor 2 (FGFR2b) isoform controls the entire program of keratinocytes differentiation, 2,3 while the FGFR2 isoform switch and the consequent aberrant expression of the mesenchymal FGFR2c isoform in epithelial context induces the impairment of differentiation, EMT and tumorigenic features, 4,5 mainly involving PKCε signalling 6 …”
Section: Introductionmentioning
confidence: 99%
“…Although the role of FGFR2c expression in the epithelial context begins to be clarified, the specific signaling network activated downstream this receptor and underlying its oncogenic outcome still remain to a large extent to be identified. Concerning this topic, we recently identified Protein Kinase Cε (PKCε)-mediated signaling as being mainly responsible for FGFR2c-mediated EMT and tumorigenic features in human keratinocytes [ 35 , 36 ]. Among the various transcription factors involved in the malignant progression and that can be therapeutically targeted [ 37 ], we found that PKCε acts downstream FGFR2c regulating Snail1, Fos-Related Antigen-1 (FRA1), and Signal Transducer and Activator of Transcription 3 (STAT3), which are induced in cascade [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning this topic, we recently identified Protein Kinase Cε (PKCε)-mediated signaling as being mainly responsible for FGFR2c-mediated EMT and tumorigenic features in human keratinocytes [ 35 , 36 ]. Among the various transcription factors involved in the malignant progression and that can be therapeutically targeted [ 37 ], we found that PKCε acts downstream FGFR2c regulating Snail1, Fos-Related Antigen-1 (FRA1), and Signal Transducer and Activator of Transcription 3 (STAT3), which are induced in cascade [ 35 ]. Actually, the activation of PKCε-mediated signaling in consequence of FGFR2 isoform switch and the involvement of this pathway in FGFR2c-mediated epidermal carcinogenesis could explain the higher occurrence of SCC in AK lesions treated with ingenol mebutate, the most common topical therapy used in the last few years for AK treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PKC-mediated signaling has been described as one of the main RAS-independent pathways activated by several receptor tyrosine kinases (RTKs), including fibroblast growth factor receptors (FGFRs) [ 6 ], whose dysregulation significantly contributes to cancer development [ 7 ]. Concerning this topic, we have recently demonstrated a central contribution for the PKCε isoform in the oncogenic outcomes established by the signaling of the mesenchymal isoform of FGFR2 (FGFR2c) when expressed in the epithelial context [ 8 , 9 ]. Even if the aberrant expressions of FGFR2c or FGFR2 altered splicing have been previously proposed as events contributing to pancreatic carcinogenesis [ 10 , 11 , 12 ], their relevance in the establishment of cell invasion, even if extensively investigated [ 10 , 11 , 12 ], remains controversial and still to be clarified.…”
Section: Introductionmentioning
confidence: 99%